C CelticDove New Member Joined Feb 25, 2016 Messages 8 Gender Female HSC 2016 Oct 2, 2016 #1 solve for x: ( 2x-1)/5 = (x/3) -1 The answer is -12 but I just don't understand how to work it out Thanks!!

solve for x: ( 2x-1)/5 = (x/3) -1 The answer is -12 but I just don't understand how to work it out Thanks!!

pikachu975 I love trials Moderator Joined May 31, 2015 Messages 2,410 Location NSW Gender Male HSC 2017 Oct 3, 2016 #2 Times 5 to both sides: 2x - 1 = 5x/3 - 5 Minus 5x/3 from both sides and add 1: x/3 = -4 Times by 3: x = -12 State ranking in general maths inc jks Last edited: Oct 3, 2016

Times 5 to both sides: 2x - 1 = 5x/3 - 5 Minus 5x/3 from both sides and add 1: x/3 = -4 Times by 3: x = -12 State ranking in general maths inc jks

J JupiterPie New Member Joined Aug 21, 2019 Messages 18 Gender Female HSC 2006 Aug 25, 2019 #3 ( 2x-1)/5 = (x/3) -1 5[( 2x-1)/5] =5[(x/3) -1] 2x - 1 = 5(x/3) - 5 2x - 1 = 5x/3 - 5 3(2x - 1) = 3(5x/3 - 5) 6x - 3 = 3(5x/3) - 3(5) 6x - 3 = 5x - 15 6x - 5x = -15 + 3 x = -12

( 2x-1)/5 = (x/3) -1 5[( 2x-1)/5] =5[(x/3) -1] 2x - 1 = 5(x/3) - 5 2x - 1 = 5x/3 - 5 3(2x - 1) = 3(5x/3 - 5) 6x - 3 = 3(5x/3) - 3(5) 6x - 3 = 5x - 15 6x - 5x = -15 + 3 x = -12